2012
DOI: 10.4314/wsa.v38i5.8
|View full text |Cite
|
Sign up to set email alerts
|

A new spectrophotometric method for determination of residual polydiallyldimethylammonium chloride flocculant in treated water based on a diazotization-coupled ion pair

Abstract: Polydiallyldimethylammonium chloride (polyDADMAC) is a water-soluble cationic polyelectrolyte used for water treatment. Its residues in treated water are contaminants as they react with chlorine to produce a carcinogenic compound. Commonly-used techniques for quantification of the polycation, such as colloidal and potentiometric titration as well as 1 H NMR, have poor sensitivity and detection limits. This paper describes a more sensitive UV spectrophotometric method for quantitative determination of residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The exchange reaction between Cl − and ClO is attributed to the interaction of ClO 4 − with CH 3 at the position 7. 35 Moreover, the x-DDA-Dex and ex-DDA-Dex hydrogel films exhibit no changes in the two chemical shifts at 71.3 and 38.5 ppm. On the other hand, 30.1 and 26.7 ppm of x-DDA-Dex hydrogel at the position 4 and 5 were moved into 27.9 and 26.6 ppm of ex-DDA-Dex hydrogel at the position 9 and 10 after the anion exchange from Cl − to ClO 4 − .…”
Section: Resultsmentioning
confidence: 97%
“…The exchange reaction between Cl − and ClO is attributed to the interaction of ClO 4 − with CH 3 at the position 7. 35 Moreover, the x-DDA-Dex and ex-DDA-Dex hydrogel films exhibit no changes in the two chemical shifts at 71.3 and 38.5 ppm. On the other hand, 30.1 and 26.7 ppm of x-DDA-Dex hydrogel at the position 4 and 5 were moved into 27.9 and 26.6 ppm of ex-DDA-Dex hydrogel at the position 9 and 10 after the anion exchange from Cl − to ClO 4 − .…”
Section: Resultsmentioning
confidence: 97%
“…16 From UV-vis based methods, various authors have reported LOD values between 0.5 mg L À1 and 1.0 mg L À1 respectively. 1,2,17,18 Our current method is a significant improvement over previous methods with a LOD of 0.54 mg L À1 .…”
Section: Development Of Analytical Protocolsmentioning
confidence: 90%
“…Stability problems can be encountered with colloidal titration techniques such as the colour change reverting back to the original starting colour or the loss of colour on standing. 17,18 To determine the resistance of the method with respect to time, a 30 mg L À1 poly-DADMAC solution was prepared, mixed with Au-NPs, and the UV-vis spectrum was recorded every 5 minutes for 50 minutes. This experiment was done in triplicate.…”
Section: Ruggedness (Robustness)mentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption of PDM on silica particles was studied by spectrophotometry based on a diazotization-coupled ion pair (Mwangi et al 2012). The absorbance of standard solutions of PDM ion pair in the range of 0.1-25.0 mg/l was measured at the wavelength of 230 nm for setting up the calibration curve.…”
Section: Adsorption Of Pdm On Silica Particlesmentioning
confidence: 99%